Substitution at sp(3) boron of a six-membered NHC center dot BH3: convenient access to a dihydroxyborenium cation - Kundu, Gargi; Ajithkumar, V. S.; Raj, K. Vipin; Vanka, Kumar; Tothadi, Srinu; Sen, Sakya S. (Chemical Communications, 2022)
Herein, we have undertaken the synthesis and investigated the reactivity of a 6-membered saturated NHC borane adduct (1). Direct electrophilic halogenation of 1 with a stoichiometric amount of I-2 led to NHC boryl iodides, 6-SIDipp center dot BH2I (2) and 6-SIDipp center dot BHI2 (3), which were further reacted with various nucleophiles to give novel 6-SIDipp based mono and disubstituted boranes with OTf (4 and 6) or ONO2 (5 and 7) functional groups. The addition of Br-2/H2O to 1 smoothly results in a dihydroxyborenium cation (8).

Synthesis of Si(IV)- and Ge(II)-substituted amines, hydrazone, and hydrazine from hypersilyl germylene - Ajithkumar, V. S.; Ghanwat, Pratiksha B.; Raj, K. Vipin; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2023)
This study investigates the reactivity of a hypersilyl germylene [PhC-(NtBu)(2)GeSi-(SiMe3)(3)] (1) with various organic compounds including azides, diazoalkanes, 1,2-diphenylhydrazine, and trifluoroacetophenone. The reactivity observed in these reactions is driven by the insertion of the organic fragment between a silicon and germanium bond. This leads to the formation of novel compounds, including an amine featuring three different substituents from three different elements of group 14. When reacting with Me3SiCHN2, we observed the insertion of the diazoalkane fragment in an end-on fashion into the Ge-Si bond. An analogous trend was observed in reactions with 1,2-diphenylhydrazine and trifluoroacetophenone, where the N-N and C-O fragments were inserted into the Ge-Si bond. Multinuclear NMR and single-crystal X-ray diffraction analyses were conducted to characterize the newly synthesized compounds.

Stereodivergent sila-germylenation vs. sila-stannylenation of an internal alkyne - Ajithkumar, V. S.; Ghanwat, Pratiksha B.; Saha, Sougata; Pati, Swapan K.; Sen, Sakya S. (CHEMICAL COMMUNICATIONS, 2024)
Keywords: DIVERSE REACTIVITY; H BOND ACTIVATION; hydrides

Sila[1]ferrocenophanes with Bulky Substituents - Ajithkumar, V. S.; Bisai, Milan Kumar; Yuvaraj, K.; Gonnade, Rajesh G.; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2025)
In this study, sila[1]ferrocenophanes with sterically bulky groups such as tris(trimethylsilyl) or N-heterocyclic iminato located at the bridging silicon atom are synthesized. The reactions of silicon-bound chloride in Fe(eta 5-C5H4)2SiCl2 (1) with K[Si(SiMe3)3] and silylated N-heterocyclic imine result in sila[1]ferrocenophanes 2 and 3 with bulky silicon- and nitrogen-based substituents at the ansa-bridge via elimination of KCl and Me3SiCl. Subsequently, the reduction of 1 is attempted using 2,3,5,6-tetramethyl-1,4-bis(trimethylsilyl)-1,4-dihydropyrazine (popularly known as Mashima reagent), which leads to the elimination of Me3SiCl and generation of 1,4-dihydropyrazine-spanned sila[1]ferrocenophanes (4). All the compounds are structurally characterized.
Keywords: ansa-bridges; ferrocenophanes; hypersilyls; Mashima reagents; N-heterocyclic imines